Penanaman Nilai-Nilai Pancasila melalui Kelas Pancasila dan Pembuatan Konten Positif Bernuansa Kebhinekaan pada Siswa-Siswi Desa Gunungsari - Septiyanto, Angga; Azzahra, Fatimah; Parmawati, Vitrianti Della; Ayu Dhea, Adinda Regitya; Suwadi, Suwadi (Universitas Negeri Semarang, 2023)
The internalization of Pancasila values in action needs to be promoted among children to strengthen national identity. The behavior of children who tend to imitate foreign cultures, be hedonistic and apathetic needs special treatment. The aim of this community service is to educate the internalization of Pancasila values and create creative content. The approach to community service activities used is Participatory Rural Appraisal (PRA) in the form of counseling, mentoring and training methods. The target community is Gunungsari State Elementary School (SD) students. The service activities will be carried out from July to August 2023. The results of the service activities are that students understand the importance of having the Pancasila character and its implementation in everyday life. The nature of mutual respect between friends, family and neighbors continues to be developed so as to create harmony and security in society. Elementary students can also behave well and positively in making friends and studying together. Keywords: Character Building, Education, Pancasila